Studi Etnobotani Rotan Sebagai Bahan Kerajinan Anyaman Pada Suku Anak Dalam (SAD) di Dusun III Senami, Desa Jebak, Kabupaten Batanghari, Jambi. - Jumiati, Jumiati; Hariyadi, Bambang; Murni, Pinta (Universitas Jambi, 2012)
Rattan is one of the non-timber forest products that has been widely used by traditional communities for various purposes such as a woven material, rigging purposes, and for other purposes. Suku Anak Dalam, SAD, is a group of indigenous people in Jambi Popinsi who still maintain a close relationship with the surrounding forests.Â The group waves rattan to produce variousrattan craft.Â This study aims to inventory the diversity of rattan species being used to prduce rattan craft and to document knowledge associated with rattan waving.Â The study was undertaken in the village of Jebak, Batanghari Regency, Jambi Province. Data collected through a semi-structured interviews and participant observation. The results indicate the presence of 10 species of rattan commonly used to manufacture various unique SAD rattan craft. The SAD produces at leart18 types of woven rattan for various purposes.